Pemetaan Batas Lahan Pondok Pesantren Entrepreneur Muhammadiyah Gondanglegi Kabupaten Malang - Azhar Adi Darmawan; Amalia Nur Adibah; Khoirul Abadi; Chairil Saleh; Suwignyo Suwignyo (Universitas Tribhuwana Tunggadewi Malang, 2021)
Modern Islamic boarding schools are a combination of Islamic boarding school curriculum with the national education curriculum. Therefore though the format is a boarding school, boarding education, students also acquire knowledge and graduation standards as students who attend public schools. The Entrepreneur Muhammadiyah Islamic Boarding School (PPEM) is a charity business unit managed by the Muhammadiyah Branch Leader (PCM) Gondanglegi, Malang Regency. The land used by the lodge is certified charity land. Along with the construction of housing on the side of cottage land, land boundaries have become a new problem between the border of cottage and housing developers. There is a difference in stake and land boundary, claimed by the housing developer next to the cottage. The target and output of this service program are that PPEM administrators can make an inventory of land through physical mapping. The product of this activity is the result of land mapping, which is applied directly in the form of a topographical mockup of the Islamic boarding school land that follows the mapping results and strengthens the land certificate.ABSTRAKSistem pondok pesantren yang modern adalah perpaduan antara kurikulum pendidikan nasional dengan kurikulum pesantren, sehingga walaupun bentuknya adalah sebuah pondok pesantren, santri juga memperoleh ilmu dan standar kelulusan seperti pelajar sekolah pada sekolah umum. Pondok Pesantren Entrepreneur Muhammadiyah (PPEM) adalah salah satu unit amal usaha di bawah pengelolaan Pimpinan Cabang Muhammadiyah (PCM) Gondanglegi, Kabupaten Malang. Lahan yang digunakan oleh pondok merupakan lahan wakaf bersertifikat. Seiring dengan pembangunan perumahan di sisi lahan pondok, batas lahan menjadi satu masalah baru, antara pengurus pondok, dengan pihak pengembang perumahan. Terdapat selisih patok dan batas lahan, yang diklaim oleh pengembang perumahan di sebelah pondok. Target dan luaran dari program pengabdian ini yaitu pengurus PPEM dapat menginventarisir lahan melalui pemetaan fisik. Produk kegiatan pengabdian masyarakat ini berupa hasil pemetaan lahan yang teraplikasikan langsung dalam bentuk maket topografi lahan pondok yang telah sesuai dengan hasil pemetaan dan memperkuat sertifikat pondok.